1998
DOI: 10.1002/(sici)1096-9071(199803)54:3<167::aid-jmv4>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized controlled trial of interleukin-2 treatment of chronic hepatitis B

Abstract: Pilot studies have demonstrated that recombinant interleukin 2 (rIL-2) has an indirect antiviral activity against hepatitis B virus, but the minimal dose of rIL-2 for induction of this effect was not defined. The aim of the study was to ascertain the most efficient dose of rIL-2 for induction of the loss of detectable serum HBV-DNA or a 50% or greater decrease in its level. Thirty-one patients with chronic hepatitis B, hepatitis B e antigen and serum HBV-DNA positive were enrolled in this double-blind randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
(18 reference statements)
1
17
0
1
Order By: Relevance
“…In controlled clinical trials, treatment with recombinant IFN-␥ or interleukin-2 in chronic hepatitis B had no antiviral effect, and there were no ALT flares. 36,37 In vitro treatment of chronically infected woodchuck hepatocytes with IFN-␥, or in vivo IFN-␥ expression in liver, did not suppress woodchuck hepatitis virus replication in chronically infected animals. 38,39 The treatment strategy in chronic hepatitis B aims to suppress HBV replication and to restore HBV-specific T-cell responses to achieve sustained remission.…”
Section: Discussionmentioning
confidence: 99%
“…In controlled clinical trials, treatment with recombinant IFN-␥ or interleukin-2 in chronic hepatitis B had no antiviral effect, and there were no ALT flares. 36,37 In vitro treatment of chronically infected woodchuck hepatocytes with IFN-␥, or in vivo IFN-␥ expression in liver, did not suppress woodchuck hepatitis virus replication in chronically infected animals. 38,39 The treatment strategy in chronic hepatitis B aims to suppress HBV replication and to restore HBV-specific T-cell responses to achieve sustained remission.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31] Standard IFN and pegylated IFN have shown potent therapeutic effects in some CHB patients and represent one of the most effective available therapeutic approaches, capable of achieving sustained control and even clearance of HBV infection in some, but not in the majority of patients with CHB. [7-10] Tilg et al have reported that a biologically active dose of IL-2 treatment was incapable of long-term therapeutic benefits in CHB patients.…”
Section: Immunotherapeutic Approaches To Chbmentioning
confidence: 99%
“…[22] This was supported by Artillo et al, who concluded that recombinant IL-2 was not useful as a monotherapy for the treatment of CHB patients after conducting a randomized, controlled trial with IL-2 in CHB patients. [23] Carenno et al have reported that IL-12 therapy in CHB patients has been endowed with considerable adverse effects, especially in higher and clinically effective doses. [24] The role of granulocyte-macrophage colony stimulating factor in cytokine production was shown by Martin et al, but the therapeutic impact of this cytokine in CHB patients has not been properly explored due to a lack of follow-up studies.…”
Section: Immunotherapeutic Approaches To Chbmentioning
confidence: 99%
“…It was found that neither a biologically active but non-toxic dose of 300,000 U of IL-2, nor a toxic dose of 1.0 million U of IL-2 resulted in sustained clearance of HBeAg in CHB patients (52). Also, notable therapeutic efficacy of IL-2 was not found in patients with CHB by Artillo et al (53). In fact, considerable reservation remains about the safety of IL-12 in CHB patients because 3 of 46 patients were withdrawn from therapy prematurely due to adverse events (54).…”
Section: Immune Therapy In Patients With Chbmentioning
confidence: 99%